Dampak Literasi Keuangan dan Gaya Hidup terhadap Perilaku Impulsive Buying Mahasiswa Gen Z: Studi Kasus Pengguna E-Wallet Dana di Politeknik Negeri Bali - I Wayan Gangga Sulaksana; Ni Made Kariati; Gede Sedana Wibawa Yasa (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
The development of e-wallets like DANA has brought convenience to digital transactions, which indirectly has the potential to trigger unplanned purchasing behavior among the younger generation. This research focuses on examining how financial literacy and lifestyle influence impulsive buying behavior among Generation Z students using the DANA application at Politeknik Negeri Bali. By applying a quantitative approach, data collection was conducted on 110 active student respondents, with the sample size drawn using the Slovin formula. All primary data obtained were then processed and analyzed using the Multiple Linear Regression method with the assistance of IBM SPSS software. The hypothesis testing results revealed three main findings. First, financial literacy has been proven to have a negative and significant impact on impulsive buying, meaning that the higher the level of financial understanding, the lower the tendency for spontaneous shopping. Second, the lifestyle variable shows a positive and significant influence, indicating that the drive of trends and lifestyle is directly proportional to the increase in the intensity of impulsive purchases. Third, together (simultaneously), financial literacy and lifestyle have a strong and significant impact on impulsive buying behavior. These findings conclude that financial literacy acts as a rational counterbalance that dampens consumer desires, while lifestyle dynamics serve as the main catalyst for impulsive transactions on digital wallet platforms.